2013
DOI: 10.1097/mph.0b013e318290cfdb
|View full text |Cite
|
Sign up to set email alerts
|

Illness Uncertainty and Quality of Life in Children With Cancer

Abstract: Illness uncertainty is prevalent and associated with lower quality of life in children diagnosed with cancer. Improved communication with children regarding disease state, treatment expectations, and prognosis may alleviate uncertainty and improve functioning in this vulnerable patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 25 publications
2
25
0
Order By: Relevance
“…This result corresponds to the finding reported by many existing studies that as illness-related distress increases, resilience (Fortier et al, 2013) and HRQOL (Molzon et al, 2017;Sharkey et al, 2017) decrease. This result corresponds to the finding reported by many existing studies that as illness-related distress increases, resilience (Fortier et al, 2013) and HRQOL (Molzon et al, 2017;Sharkey et al, 2017) decrease.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This result corresponds to the finding reported by many existing studies that as illness-related distress increases, resilience (Fortier et al, 2013) and HRQOL (Molzon et al, 2017;Sharkey et al, 2017) decrease. This result corresponds to the finding reported by many existing studies that as illness-related distress increases, resilience (Fortier et al, 2013) and HRQOL (Molzon et al, 2017;Sharkey et al, 2017) decrease.…”
Section: Discussionsupporting
confidence: 91%
“…Third, this study verified that illness-related distress, social support, hope and defensive coping had indirect effects on resilience and the level of indirect effects on HRQOL was in the order of illness-related distress, social support, defensive coping, hope and courageous coping. This result corresponds to the finding reported by many existing studies that as illness-related distress increases, resilience (Fortier et al, 2013) and HRQOL (Molzon et al, 2017;Sharkey et al, 2017) decrease. Furthermore, among adolescents with significant social support, the levels of resilience (Haase et al, 1999(Haase et al, , 2014Hong & Park, 2015) and HRQOL (Arabyat & Raisch, 2015;Gonzalez-Saenz de Tejada et al, 2017) are high.…”
Section: Discussionsupporting
confidence: 91%
“…27 Perhaps the most obvious and important intervention strategy to decrease uncertainty is increased skillful communication by healthcare providers that is timely, developmentally appropriate, and empathically delivered regarding diagnosis, prognosis, and what to expect during their treatment course. 24 Because cancer-related information is often complex, ambiguous, and emotionally difficult, providing written information and/or directing AYA to age-relevant information sources, such as web-sites, may be a helpful component of an uncertainty intervention. To take in, understand, make decisions about, and act on information relevant to their cancer journey, interventions designed to support effective expression and communication of their thoughts and emotions are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have been showed that talking with children about their illnesses reduces their anxiety and depression [2]. Conversely, if children received no information or lack of information about illnesses, they experienced negative emotions because of the illness uncertainty [3]. Some children experience childhood cancer to be stressful and traumatic [4,5].…”
Section: Page 3/24mentioning
confidence: 99%